2005
DOI: 10.1037/0033-2909.131.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Adoption and Cognitive Development: A Meta-Analytic Comparison of Adopted and Nonadopted Children's IQ and School Performance.

Abstract: This meta-analysis of 62 studies (N=17,767 adopted children) examined whether the cognitive development of adopted children differed from that of (a) children who remained in institutional care or in the birth family and (b) their current (environmental) nonadopted siblings or peers. Adopted children scored higher on IQ tests than their nonadopted siblings or peers who stayed behind, and their school performance was better. Adopted children did not differ from their nonadopted environmental peers or siblings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
259
3
19

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 401 publications
(296 citation statements)
references
References 97 publications
(118 reference statements)
15
259
3
19
Order By: Relevance
“…These findings are partly consistent with our study in that there was an effect of social class of approximately the same magnitude for general cognitive abilities within dizygotic pairs as within siblings for their measure of IQ. However, our absence of evidence for childhood social class influences after fully controlling for genetic confounds [genetic influences on both cognition and educational attainment (20)] differs from previous studies using adoption data (10,11). The monozygotic within-pair analysis provides a more complete control of genetic confounds than the within-sibpair comparisons by Kendler et al (11).…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…These findings are partly consistent with our study in that there was an effect of social class of approximately the same magnitude for general cognitive abilities within dizygotic pairs as within siblings for their measure of IQ. However, our absence of evidence for childhood social class influences after fully controlling for genetic confounds [genetic influences on both cognition and educational attainment (20)] differs from previous studies using adoption data (10,11). The monozygotic within-pair analysis provides a more complete control of genetic confounds than the within-sibpair comparisons by Kendler et al (11).…”
Section: Discussioncontrasting
confidence: 52%
“…Thus, to more fully understand the role of social class on cognition there is a need for use of genetically informative samples. A metaanalysis of adoption and cognitive development showed that adoption to a family with higher social class had a positive effect on IQ of the adoptees compared with nonadopted biological siblings (10). Using data on home-reared and adoptedaway siblings, Kendler et al (11) found that IQ in late adolescence/young adulthood (age 18 y) was associated with the rearing environment, and that the observed differences in IQ were related to the rearing parents' level of education.…”
mentioning
confidence: 99%
“…IQ gains as large as 19.5 have been found among children adopted by high SES families at ages 4-6 and who had experienced abuse or neglect (Duyme, Dumaret, & Tomkiewcz, 1999). A recent meta-analysis showed that adopted children's IQ scores exceeded those of their non-adopted biological siblings and peers who remained with their birth families or in institutional care (Van Ijzendoorn, Juffer, & Poelhuis, 2005). The adopted children's scores did not differ from those of their non-adopted siblings (the children with whom they were raised) or their peers.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis has reported that national and international adoptees do not perform as well as non-adopted children of the same age at school while there are only ''negligible'' differences in IQ [7]. The authors introduced the term ''adoption decalage'' to describe the discrepancy between cognitive prerequisites (IQ) and school performance and related this to ''socio-emotional problems related to their adoption status''.…”
Section: Introductionmentioning
confidence: 99%